2016
DOI: 10.19173/irrodl.v17i1.2176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Online Log Variables that Estimate Learners’ Time Management in a Korean Online Learning Context

Abstract: The purpose of this study was to identify the relationship between the psychological variables and online behavioral patterns of students, collected through a Learning Management System (LMS). Test was attempted of a structural equation model representing the relationships among Time and Study Environment Management (TSEM), one of the sub-constructs of MSLQ, influencing a set of time-related online log variables: login frequency, login regularity, and total login time. Data were collected from 188 college stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
1
38
1
1
Order By: Relevance
“…Time management is defined as the ability to prioritize time in order to fulfill learning demands, complete tasks, and modify plans to accommodate any changes in time or demands (Jo, Park, Yoon, & Sung, 2016). Time management has been shown to be a significant predictor of online achievement (Jo et al, 2016;Kwon, 2009;Choi & Choi, 2012), although the association may be weak (r=.14, p=.00; Broadbent & Poon, 2015).…”
Section: Factors Related To Achievement In Online Coursesmentioning
confidence: 99%
See 3 more Smart Citations
“…Time management is defined as the ability to prioritize time in order to fulfill learning demands, complete tasks, and modify plans to accommodate any changes in time or demands (Jo, Park, Yoon, & Sung, 2016). Time management has been shown to be a significant predictor of online achievement (Jo et al, 2016;Kwon, 2009;Choi & Choi, 2012), although the association may be weak (r=.14, p=.00; Broadbent & Poon, 2015).…”
Section: Factors Related To Achievement In Online Coursesmentioning
confidence: 99%
“…Procrastination in general is thought to be negatively associated with course performance, and this might explain our finding (e.g., Tice & Baumeister, 1997). Other studies have found that time management in online courses predicts achievement (Jo et al, 2016;Kwon, 2009;Choi & Choi, 2012). Alternatively, this variable could simply reflect that students who were struggling in the course found it difficult to grade these assignments (i.e., it's hard to determine if something is right or wrong if you yourself are unsure of the right answer), and therefore took longer to submit it.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Numerous studies investigating theoretical and applied aspects of distance and online learning have been published. However, the problem of effectively supporting successful student learning still persists (Jo et al, 2016). To gain insight into this problem, one line of research has focused on the characteristics and skills of distance and online learners and the extent to which they predict learning processes and outcomes.…”
Section: Introductionmentioning
confidence: 99%